Soft Skills Level of Malaysian Students at a Tertiary Institution: A Comparative Case Study Based On Gender, Area of Residence and Type of Schools - Ahmad, Shariffah Bahyah Syed (International Journal of Asian Social Science, 2013)
The development of soft skills has been a major concern in the Malaysian higher education scene. In order to identify appropriate strategies in developing these skills among students, it is important for institutions to be aware of soft skill levels of students before they start a degree programme. This paper reports the findings of a study on the soft skill levels of students from the foundation and the diploma programmes of a private institution of higher learning. It includes comparative analyses of the results in terms of gender, area of residence and type of schools.